Geologi dan Studi Kasus Kuat Tekan Breksi Andesit Sebagai Agregat Material Beton di Desa Kadaleman dan Sekitarna, Kecamatan Surade, Kabupaten Sukabumi, Provinsi Jawa Barat - Anjas Alby Riant,; Dianto Isnawan,; M Rizqy Mahbub, (ReTII, 2023)
The study was undertaken in Kadaleman and Surrounding Areas of the Surade Sub-district, Sukabumi Regency, West Java Province. This research aimed to employ andesites based on stones' physical and mechanical properties. The research was conducted by obtaining primary data and sampling. A petrographic study was performed to determine the optical properties of the mineral constituents of stones. On the other hand, uniaxial compressive strength analysis was performed to determine the engineering properties of stones. The petrographic analysis of andesite breccias in the area revealed a mineral composition consisting of plagioclase, opaque minerals, quartz, hornblende, glass, and a fundamental mass of volcanic glass with a good level of resistance. The compressive strength of andesite breccia in the LP-101 sample was 720.813 kg/cm2l; on the other hand, the LP-25 selection was 245.694 kg/cm2. The difference in value was related to the different levels of stone weathering and porosity. The stone is classified as medium-strong based on the compressive strength test. Andesite breccia in the research region can be utilised for materials of ceramic, pavement floor covering, roadside brick pillars, and class I heavy concrete construction based on the quality standards of natural stone for construction (SII 0378-80). According to the Standards of the Directorate General of Highways (1979), andesite breccia can be utilised in the field as a material for house construction, road construction, and concrete piles.